H∞ state estimation for discrete memristive neural networks with signal quantization and probabilistic time delay. Issue 1 (1st January 2021) - Feng, Le; Zhao, Liang; Ban, Liqun
Abstract : In this paper, the problem of H ∞ state estimation is discussed for a class of delayed discrete memristive neural networks with signal quantization. A random variable obeying the Bernoulli distribution is used to describe the probabilistic time delay. A switching function is introduced to reflect the state dependence of memristive connection weight on neurons. Our aim is to design a state estimator to ensure that the specified disturbance attenuation level is guaranteed. By using Lyapunov stability theory and inequality scaling techniques, the specific explicit expression of gain parameter is given. Finally, a numerical example is given to verify the effectiveness of the proposed estimation method.